Atypical chemokine receptor ACKR3/CXCR7 controls postnatal vasculogenesis and arterial specification by mesenchymal stem cells via Notch signaling - Wei, Sung-Tai (Cell Death Dis, 2020)
Mesenchymal stem cells (MSCs) are known to play a role in postnatal vasculogenesis and hold great promise for vascular regeneration. However, the mechanisms by which the endothelial differentiation and specification of MSCs remain unclear. We examined the potential role and molecular mechanisms of atypical chemokine receptor ACKR3/CXCR7 in MSC-mediated endothelial cell differentiation and specification. Here, we showed that vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) activate CXCR7 expression on MSCs through PDGF receptors, PDGFRα and PDGFRβ-mediated phosphoinositide 3-kinase (PI3K)/Akt signaling. Genetic and pharmacologic blockage of CXCR7 on MSCs suppressed the VEGF or stromal cell-derived factor 1 (SDF)-1-induced the capacity for vasculogenesis in vitro and in vivo. Moreover, CXCR7 gain of function markedly promoted vasculogenesis by MSCs in vitro and in vivo and induced endothelial differentiation along the arterial endothelial cell lineage via upregulation of Notch signaling. However, blockade of Notch signaling inhibited CXCR7-induced vasculogensis by MSCs. These results indicate CXCR7 is a critical regulator of MSC-mediated postnatal vasculogenesis and arterial specification via Notch signaling.